Band alignment at InP/TiO2 interfaces from density-functional theory - Ruiz Alvarado, Isaac Azahel; Dreßler, Christian; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
Abstract The natural band alignments between indium phosphide and the main dioxides of titanium, i.e. rutile, anatase, and brookite as well as amorphous titania are calculated from the branch-point energies of the respective materials. Irrespective of the titania polymorph considered, type-I band alignment is predicted. This may change, however, in dependence on the microscopic interface structure: supercell calculations for amorphous titania grown on P-rich InP(001) surfaces result in a titania conduction band that nearly aligns with that of InP. Depending on the interface specifics, both type-I band and type-II band alignments are observed in the simulations. This agrees with recent experimental findings.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

LiNbO3 surfaces from a microscopic perspective - Sanna, Simone; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Advanced capabilities for materials modelling with Quantum ESPRESSO - Giannozzi, P; Andreussi, O; Brumme, T; Bunau, O; Buongiorno Nardelli, M; Calandra, M; Car, R; Cavazzoni, C; Ceresoli, D; Cococcioni, M; Colonna, N; Carnimeo, I; et al. (Journal of Physics: Condensed Matter)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

The effect of (NH4)2Sxpassivation on the (311)A GaAs surface and its use in AlGaAs/GaAs heterostructure devices - Carrad, D J; Burke, A M; Reece, P J; Lyttleton, R W; Waddington, D E J; Rai, A; Reuter, Dirk; Wieck, A D; Micolich, A P (Journal of Physics: Condensed Matter)

Elemental distribution, solute solubility and defect free volume in nanocrystalline restricted-equilibrium Cu–Ag alloys - Riedl, Thomas; Kirchner, A; Eymann, K; Shariq, A; Schlesiger, R; Schmitz, G; Ruhnow, M; Kieback, B (Journal of Physics: Condensed Matter)
In this article we study the elemental distribution and solute solubility in nanocrystalline alloys of immiscible components near restricted equilibrium for the case of the binary Cu–Ag system. As predicted from thermodynamic considerations, a grain boundary segregated monophase alloy is observed in the annealed mechanically alloyed state for low Ag content by using atom probe tomography. From the detected Ag solute grain boundary enrichment the segregation free enthalpy is estimated to range between -25 and -49 kJ mol^-1 following the McLean equation, in agreement with values reported for coarse-grained Cu–Ag. The extension of the alloying range is described by a two-domain thermodynamic model that considers the excess free volume in the grain boundaries and the strain in the strain interior on the basis of the universal equation of state at negative pressure. To access the grain boundary volumetric strain experimentally, a method based on a combination of density measurements and microscopical quantification of closed pore areas is presented. Moreover, we apply x-ray diffraction line broadening analysis to determine the local strain amplitude, which yields a root-mean-square microstrain of 0.3% for a grain size of 30 nm. It is shown that the grain boundary free volume represents the major origin for the global solubility enhancement in nanocrystalline Cu–Ag at 503 K.

Photoluminescence lineshape features of carbon δ-doped GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Spin resolved photoelectron spectroscopy of [Mn6IIICrIII]3 +single-molecule magnets and of manganese compounds as reference layers - Helmstedt, Andreas; Müller, Norbert; Gryzia, Aaron; Dohmeier, Niklas; Brechling, Armin; Sacher, Marc; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail; et al. (Journal of Physics: Condensed Matter)
Keywords: Condensed Matter Physics; General Materials Science

Glutamic acid adsorbed on Ag(110): direct and indirect molecular interactions - Blankenburg, S; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

QUANTUM ESPRESSO: a modular and open-source software project for quantum simulations of materials - Giannozzi, Paolo; Baroni, Stefano; Bonini, Nicola; Calandra, Matteo; Car, Roberto; Cavazzoni, Carlo; Ceresoli, Davide; Chiarotti, Guido L; Cococcioni, Matteo; Dabo, Ismaila; Dal Corso, Andrea; de Gironcoli, Stefano; et al. (Journal of Physics: Condensed Matter)

Coherent optoelectronics with single quantum dots - Zrenner, Artur; Ester, P; Michaelis de Vasconcellos, S; Hübner, M C; Lackmann, L; Stufler, S; Bichler, M (Journal of Physics: Condensed Matter)
The optical properties of semiconductor quantum dots are in many respects similar to those of atoms. Since quantum dots can be defined by state-of-the-art semiconductor technologies, they exhibit long-term stability and allow for well-controlled and efficient interactions with both optical and electrical fields. Resonant ps excitation of single quantum dot photodiodes leads to new classes of coherent optoelectronic functions and devices, which exhibit precise state preparation, phase-sensitive optical manipulations and the control of quantum states by electrical fields.

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)